Kajian Hambur Balik Akustik Dari Tukik Penyu Lekang (Lepidochelys olivacea) Melalui Pengukuran Secara Terkontrol Pada Frekuensi 200 kHz - Irwin Wahyudi; Deddy Bakhtiar; Ari Anggoro (Barakuda'45, 2021)
Turtles are marine reptiles that are protected because of their endangered population. The Convention on International Trade in Endangered of Wild Flora and Fauna (CITES) stipulates seven species of sea turtles in the world into Appendix I as endangered, protected and not exploited in any form. The number of hatchlings that managed to reach the sea is currently difficult to know, one method that can be used to detect the presence of hatchlings in nature is by using the acoustic method. This study aims to analyze the backscatter characteristics of the turtle hatchlings and to determine the relationship between backscattering and body length of the turtle hatchlings. The benefits of this research are expected to be able to provide information about the value of backscatter and the relationship to the body length of hatchlings that can be used as a basis for estimating the stock or abundance of hatchlings in nature. This research was conducted in the waters of the Tapak Padri pond, Bengkulu City. The research implementation takes about 3 months, from August to October 2020. Acoustic data processing is carried out at the Marine Acoustic and Resource Exploration Laboratory, Marine Department, FMIPA, Sriwijaya University, Palembang. The results obtained are that the average value of TS ranges from -52.74 to -48.45 dB for hatchlings length of 7-9.3 cm. Based on the regression equation, the coefficient of determination (R2) obtained is 0.57, so it is known that the total length affects the target strength value by 57% and 43% is influenced by other factors. it can be concluded that there is a relationship between the total length of the hatchlings with the TS value of the hatchlings or the total length has an influence on the magnitude of the TS value in the hatchlings.